Pelaksanaan Proses Belajar Mengajar Pendidikan Jasmani Olahraga dan Kesehatan pada Sekolah Dasar - Muhammad Supriyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this research is to know how the method of teaching, and infrastructure facilities of Physical Education of Sport and Health at State Elementary School 23 5 East Koto Padang Pariaman Regency. His research method descriptive research finds that the implementation of teaching and learning process of physical education practice in health and elementary school Country 23 V Koto Timur Padang Pariaman District is as follows: in terms of teaching methods with demonstration indicators have the average number of answers 80 times 50 percent with medium criteria and lecture indicator has the average number of answers 136 times 60.71 percent. For facilities and infrastructure with sports equipment indicator have average percentage of student answer 130 times 50.78 percent with medium criterion. From the above results can be concluded that the implementation of teaching and learning process physical exercise and health education in Public Elementary School 23 5 East Koto Padang Pariaman Regency is inthecategory of being. Keywords: Teaching and Learning Process, Physical Education Sport and Health